Perinatal Stress and Methamphetamine Exposure Decreases Anxiety-Like Behavior in Adult Male Rats - Holubová-Kroupová, Anna; Šlamberová, Romana (Frontiers in Behavioral Neuroscience, 2021)
Methamphetamine (MA) is an illicit synthetic psychostimulant drug, and its abuse is growing worldwide. MA has been reported as the primary drug of choice, by drug-abusing women, during pregnancy. Since MA easily crosses the placental barrier, the fetus is exposed to MA in a similar fashion to the mother. This study aimed to evaluate the effect of long-term perinatal stressors and drug exposure on anxiety-like behavior in adult male rats using the open field test (OF) and elevated plus maze (EPM). Dams were divided into three groups according to drug treatment during pregnancy: controls (C); saline - SA (s.c., 1 ml/kg); MA (s.c., 5 mg/kg). Litters were divided into four groups according to postnatal stressors: non-stressed controls (N), maternal separation (S); maternal cold-water stress (W); and maternal separation plus maternal cold water stress (SW). Forty-five minutes before testing (in both OF and EPM), one-half of adult male rats received an (s.c.) injection of MA and the other half received an SA injection. Prenatal MA/stress exposure did not affect anxiety-like behavior in adult male rats in both tests. In the OF, an acute MA dose in adulthood increased the time spent in the central disc area, decreased time spent in the corners, and decreased time spent immobile and grooming. Also, postnatal stress increased time spent in the central disc area, decreased time spent in corners and increased mobility compared to controls. All groups of rats exposed to postnatal stressors spent significantly less time in the closed arms of the EPM compared to controls. Overall, our results indicate that early postnatal stress and a single acute MA administration in adulthood decreases the parameters of anxiety-like behavior in adult male rats regardless of prenatal MA exposure. Moreover, postnatal stress via maternal separation impacts the effect of acute MA administration in adulthood. Long-term postnatal stress may thus result in improved adaptation to subsequent stressful experiences later in life.